ESTABLISHMENT OFAWIRELESS NETWORK FOR INDUSTRIAL ENTERPRISES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The useof wireless networks in industrial enterprises and its advantages are highlighted. Ways to use a wireless network for a few. This network provides practical solutions to existing problems in the management of industrial enterprises. They provide insights into the differences between wireless networks and the requirements imposed on them.